2006
DOI: 10.4049/jimmunol.176.7.4337
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of TLR2 and the Adaptor ASC in IL-1β/IL-18 Secretion in Response to Listeria monocytogenes

Abstract: Apoptosis-associated speck-like protein containing a C-terminal caspase recruitment domain (ASC) is an adaptor molecule that has recently been implicated in the activation of caspase-1. We have studied the role of ASC in the host defense against the intracellular pathogen Listeria monocytogenes. ASC was found to be essential for the secretion of IL-1β/IL-18, but dispensable for IL-6, TNF-α, and IFN-β production, in macrophages infected with Listeria. Activation of caspase-1 was abolished in ASC-deficient macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 27 publications
7
101
0
1
Order By: Relevance
“…This finding is consistent with the observation that Nod2 and RICK cooperate with TLR signaling for optimal responses to TLR ligands. The innate immune response to Listeria, including cytokine production, also involves TLR signaling particularly through TLR2 (22,24). Consistent with these finding, we observed that in the absence of RICK there was a considerable residual cytokine response induced by Listeria in macrophages.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is consistent with the observation that Nod2 and RICK cooperate with TLR signaling for optimal responses to TLR ligands. The innate immune response to Listeria, including cytokine production, also involves TLR signaling particularly through TLR2 (22,24). Consistent with these finding, we observed that in the absence of RICK there was a considerable residual cytokine response induced by Listeria in macrophages.…”
Section: Discussionsupporting
confidence: 87%
“…The early recognition of Listeria involves activation of TLRs at the plasma membrane and endosomes as well as in the cytosol via NLRs and receptors involved in nucleic acid recognition (22)(23)(24). To assess the contribution of RICK in the cytokine response induced by live Listeria, WT and RICK-deficient macrophages were infected with the bacterium and the production of cytokines was determined 12 and 24 h postinfection.…”
Section: Rick Contributes To Cytokine Responses Induced By Live Listementioning
confidence: 99%
“…[39][40][41][42][43] Interestingly, NLRP3 also contributes to the ability of dendritic cells and macrophages to detect endogenous danger molecules released by dying cells. NLRP3 can signal the presence of adenosine triphosphate (ATP), crystals of monosodium urate (MSU) or calcium pyrophosphate crystals, 39,44 and other large particulates of non-microbial origin, such as alum, silica and asbestos ( Figure 2).…”
Section: Genetics Of the Inflammasomes In Human Pathologiesmentioning
confidence: 99%
“…The most important TLR for L. monocytogenes recognition appears to be TLR2. TLR2-deficient macrophages after in vitro infection with L. monocytogenes secrete less TNFα, IFNγ, IL-1β and IL-12 [39][40][41]. However, mice deficient in TLR2 have little increase in bacterial burden compared to wild-type mice [40].…”
Section: Toll-like Receptor Recognitionmentioning
confidence: 99%